An Increase in Membrane Cholesterol by Graphene Oxide Disrupts Calcium Homeostasis in Primary Astrocytes. Issue 15 (20th March 2019) - Bramini, Mattia; Chiacchiaretta, Martina; Armirotti, Andrea; Rocchi, Anna; Kale, Deepali D.; Martin, Cristina; Vázquez, Ester; Bandiera, Tiziano; Ferroni, Stefano; Cesca, Fabrizia; Benfenati, Fabio
Abstract: The use of graphene nanomaterials (GNMs) for biomedical applications targeted to the central nervous system is exponentially increasing, although precise information on their effects on brain cells is lacking. In this work, the molecular changes induced in cortical astrocytes by few‐layer graphene (FLG) and graphene oxide (GO) flakes are addressed. The results show that exposure to FLG/GO does not affect cell viability or proliferation. However, proteomic and lipidomic analyses unveil alterations in several cellular processes, including intracellular Ca 2+ ([Ca 2+ ]i ) homeostasis and cholesterol metabolism, which are particularly intense in cells exposed to GO. Indeed, GO exposure impairs spontaneous and evoked astrocyte [Ca 2+ ]i signals and induces a marked increase in membrane cholesterol levels. Importantly, cholesterol depletion fully rescues [Ca 2+ ]i dynamics in GO‐treated cells, indicating a causal relationship between these GO‐mediated effects. The results indicate that exposure to GNMs alters intracellular signaling in astrocytes and may impact astrocyte–neuron interactions. Abstract : Alterations in several cellular processes in cortical astrocytes exposed to graphene oxide (GO), including intracellular Ca 2+ ([Ca 2+ ]i ) homeostasis and cholesterol metabolism, are found and investigated. GO exposure impairs spontaneous and evoked astrocyte [Ca 2+ ]i signals and induces a marked increase in membrane cholesterol levels. Importantly, cholesterol depletion fully rescues [Ca 2+ ]i dynamics in GO‐treated cells, indicating a causal relationship between these GO‐mediated effects.